1987
DOI: 10.1017/s0003356100002889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body condition, food intake and temporary calf separation on the duration of the post-partum anoestrous period and associated LH, FSH and prolactin concentrations in beef cows

Abstract: An experiment was conducted to examine factors affecting the length of the post-partum anoestrous period and associated effects on LH, FSH and prolactin. Forty-six cows (24 Hereford × Friesian and 22 Blue-Grey) ranging in body condition score at calving from 1·50 to 2·75 were used. They were individually fed chopped barley straw and concentrate at either 50 (low) or 91 (high) MJ metabolizable energy per day from calving. At 34 days post partum half the cows were separated from their calves for 48 h. The durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
9

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 24 publications
4
23
0
9
Order By: Relevance
“…Wright et al (1987) attribute a 43-day reduction in postcalving anoestrus for each point of increase in body condition score at calving.…”
Section: Resultsmentioning
confidence: 99%
“…Wright et al (1987) attribute a 43-day reduction in postcalving anoestrus for each point of increase in body condition score at calving.…”
Section: Resultsmentioning
confidence: 99%
“…El acceso libre del ternero a la madre se relacionó con reactivaciones ováricas medias y sobre todo largas, a pesar de que tanto antes como después del parto los animales tendieron a presentar ganancias de peso, como han observado otros autores (San Juan et al, 1994;Stagg et al, 1998). La mayoría de los trabajos realizados al respecto coinciden en señalar un aumento en la liberación pulsátil de LH después del destete del ternero (Whisnant et al, 1985;Rund et al, 1989), o de la restricción del acceso del ternero a la madre (Stagg et al, 1998;Diskin et al, 1999;Sanz et al, 2000), o de la separación del ternero durante 48 horas (Wright et al, 1987). Este trabajo corrobora que la restricción del acceso del ternero a la madre es una técnica sencilla y económi-ca, que facilitará que los animales reinicien la actividad reproductiva de forma temprana.…”
Section: Discussionunclassified
“…Se consideró que la actividad ovárica se iniciaba cuando se detectó la primera elevación de los valores reales de progesterona por encima de 0,5 ng/ml durante al menos dos días, o 1 ng/ml en un sólo día, concentraciones que reflejaban la existencia de actividad luteal y/o placentaria (Thimonier, 1978). En las vacas que no presentaron reactivación ovárica durante el periodo controlado se consideró como duración del APP el intervalo entre el parto y la última muestra de sangre recogida (Wright et al, 1987), coincidiendo con la duración de la lactación (140 y 170 días, para los partos de otoño y primavera, respectivamente).…”
Section: Análisis Hormonalunclassified
See 1 more Smart Citation
“…A PPA period less than 85-100 days is required if cows are to have the opportunity to produce a calf each year (Peters & Lamming 1986;Wright et al 1987 Nutrition is the key limitation to reproduction as differences in nutritional status of animals across the various sites involved with this study were observed as reflected in the differences in BCS. The main feed types used by farmers are rice straw, native grass, elephant grass, Sesbania, Gliricidia and peanut straw.…”
Section: Resultsmentioning
confidence: 99%